SISTEM MANAJEMEN ORGANISASIONAL, SUMBERDAYA MANUSIA, DAN PEMENUHAN KEBUTUHAN PASAR KERAJINAN KULIT - Andrus Margiono (Jurnal Riset Manajemen dan Bisnis, 2012)
Organizational management system combines all management functions within anorganization's productive holistically built based on the concept of quality, teamwork,productivity and customer satisfaction. Be as creative industries leather craft is required tofollow the changes and able to meet the needs of the market. Change the orientation of themarket take effect directly against the durability of micro, small and medium-sized leathercraft, it takes a flexible company management system in maintaining continuity of effort, thatit took creativity and innovation on an ongoing basis. Among the many leather companies inYogyakarta were selected for this study are “CV D & D Leather Handycraft”. Throughmultiple regression analysis, the results showed that the company's organizationalmanagement system to fulfill the needs of the market demand for leather products. Likewise,the development of human resources for creative and innovative to the fulfillment of the needsof the market demand of products leather craft.Keywords: A system of organizing, human resources, the fulfillment of market needs